Tailored setting times with high compressive strengths in bassanite calcium sulfoaluminate eco-cements - García-Maté, Marta; Londono-Zuluaga, Diana; Gómez-de-la-Torre, María de los Ángeles; Ramírez-Losilla, Enrique; Cabeza-Díaz, Aurelio; García-Aranda, Miguel Ángel; Santacruz-Cruz, María Isabel (Elsevier, 2016)
This work deals with the hydration of a calcium sulfoaluminate (CSA) eco-cement prepared with bassanite and different additives (type and content) at a fixed water/CSA ratio of 0.5. Pastes prepared with bassanite show high water demands, high viscosity values and short initial setting times which are related to the fast dissolution rate of bassanite and the subsequent precipitation of gypsum. These facts have a dramatic effect onto the mechanical strength values, and make necessary the addition of additives. Here, the addition of different amounts of specific retarders (polycarboxylate, tartaric acid and phosphonic acid) not only improved the workability of pastes and mortars, but also delayed the setting time, by modifying the dissolution rates of the phase(s), and improved mechanical strengths. Finally, mortars with high compressive strengths (46 and 84 MPa at 1 and 7 days of hydration, respectively) and, chiefly, tailored setting times with high strengths have been prepared.
Keywords: Cristalografía por rayos X; Cemento; X-Ray Diffraction analysis; Hydration; Compressive Strength; Sulfoaluminate